MASSACHUSETTS ACTION REQUEST. - MOZINGO RL (Tufts Archival Research Center, 2007)
Tobacco Action Network request for Massachusetts action. Provides background on proposed MA legislation. Lists direct lobbying plans. Discusses legislative support. Requests permission to ask memver companies to write to legislators and participate in a petition drive, and telephone bank, and a flyer distribution program. Mentions additional plans.